Endodontic-orthodontic interrelationship: a review. - Mustaffa, Musliana; Nasir, Siti Hajjar (IIUM Press, 2021)
The endodontic-orthodontic interface is not well understood due to the limited scientific literature on the topic. This article aims to provide an overview of the orthodontic treatment and the risk of root resorption, the effects of orthodontic tooth movement on dental pulp and endodontically treated teeth, the role of orthodontics in endodontic-restorative treatment planning, and interdisciplinary patient management. Articles published in English from 1982 to 2021 were searched manually from google scholar using keywords ‘endodontic-orthodontic interface’ and ‘endodontic-orthodontic interrelationship’. Another search engine was MEDLINE/PubMed database using keywords ‘endodontics AND orthodontics’, ‘orthodontic tooth movement AND dental pulp’, 'orthodontic tooth movement AND endodontic treatment' and 'orthodontics AND dental trauma'. Other relevant articles were obtained from the references of the selected papers. Alterations to the dental pulp following orthodontic tooth movement can be histologic and/or cell biological reactions as well as the increased response threshold to pulp sensibility tests. However, the occurrence of root resorption is complex and multifactorial, and can be linked to individual variation, genetic predisposition and orthodontic treatment-related factors. Endodontically treated teeth can move as readily and respond similarly to orthodontic forces as vital teeth, however with inadequate endodontic treatment, the risk of apical inflammation and bone destruction following orthodontic tooth movement is increased. Dental treatment that involves endodontic and orthodontic specialities should be carefully planned according to the individual case, taking into consideration the skills and experience of the clinicians while applying interdisciplinary patient management and available scientific data.